Semantic Change in Javanese Kinship Term of Address: A Case Study in Gedang Kulut Village, Gresik District - Ahmad Muzaki (Centre for Literary and Cultural Studies, 2023)
Within the development of the era, the meaning of the words also developed and changed. One of the word-meaning conversions in society is the conversion of the term of address, particularly in kinship relationships. A case study in Gedang Kulut Village revealed that the word of speech Cak (Old Brother) and Mbak (Old Sister) is not only used to call the old brother and sister but also refers to the Man (Uncle) and Bebek (Aunt). The other conversion uses Pak De (Uncle) and Mak De (Aunt) to substitute the term of address for grandmother and grandfather. The paper aims to analyse the representation of speech in the Javanese language used in Gedang Kulut Village, Gresik District. The methodology uses a descriptive qualitative method that also emphasises the semantics approach. The result shows a unique word-meaning conversion in the Javanese term of address used in Gedang Kulut Village. Moreover, the mutation appearing in the word of speech causes the social marks to change either up or down.